The Effects of α-Chaconine on ER-α Positive Endometrium Cancer Cells - Ayşe Kübra Karaboğa Arslan; Mükerrem Betül Yerer (Proceedings, 2017)
Endometrial cancer is one of the most common cancer types among women in the world. In our study, it was aimed to investigate the potential anticancer effect of α-chaconine, which is one of the major glycoalkaloids found in Solanum tuberosum (potato), on estrogen receptor (ER) positive endometrial cancer cell line RL95-2. The effect of α-chaconine on RL95-2 cell viability was determined by the method of sulforhodamine B. Effect of α-chaconine on cell growth curve was assessed with the real-time cell analyzer system (xcelligence). The ERα inhibitor methyl-piperidino-pyrazole (MPP) dihydrochloride was used as a positive control to evaluate the association of α-chaconine with ERα. Expressions of ERα and p-ERα protein level were investigated by western blot. ERα mRNA expressions were performed by the real-time PCR method. The IC50 values ​​ of MPP dihydrochloride and α-chaconine were calculated as 20.01 μM and 4.72 μM, respectively. At MPP dihydrochloride 20 μM (p < 0.001), α-chaconine; 2.5 (p < 0.001); 5 (p < 0.001) and 10 μM (p < 0.001) concentrations, p-ERα/ERα ratio was decreased in the same significance compared to control. α-Chaconine decreased the level of ERα mRNA expression, after 24 h, but this decrease was not significant. This study showed for the first time the effect of α-chaconine on cell proliferation, ERα activity and expression in RL95-2 cells.